A review of the direct targets of the cannabinoids cannabidiol, Δ9-tetrahydrocannabinol, N-arachidonoylethanolamine and 2-arachidonoylglycerol - Wright, Nicholas J. D. (AIMS neuroscience, 2024)
Marijuana has been used by humans for thousands of years for both medicinal and recreational purposes. This included the treatment of pain, inflammation, seizures, and nausea. In the 1960s, the structure of the principal psychoactive ingredient Δ9-tetrahydrocannabinol was determined, and over the next few decades, two cannabinoid receptors were characterized along with the human endocannabinoid system and what it affects. This includes metabolism, the cardiovascular and reproductive systems, and it is involved in such conditions as inflammation, cancer, glaucoma, and liver and musculoskeletal disorders. In the central nervous system, the endocannabinoid system has been linked to appetite, learning, memory, and conditions such as depression, anxiety, schizophrenia, stroke, multiple sclerosis, neurodegeneration, addiction, and epilepsy. It was the profound effectiveness of cannabidiol, a non-psychoactive ingredient of marijuana, to relieve the symptoms of Dravet syndrome, a severe form of childhood epilepsy, that recently helped spur marijuana research. This has helped substantially to change society's attitude towards this potential source of useful drugs. However, research has also revealed that the actions of endocannabinoids, such as anandamide and 2-arachidonoylglycerol, and the phytocannabinoids, tetrahydrocannabinol and cannabidiol, were not just due to interactions with the two cannabinoid receptors but by acting directly on many other targets including various G-protein receptors and cation channels, such as the transient receptor potential channels for example. This mini-review attempts to survey the effects of these 4 important cannabinoids on these currently identified targets.